Software para análise de dimensionamento de reatores CSTR em regime transiente utilizando linguagem python - Romano, Rafael (2023)
In the chemical engineering field more especifically about projects involving chemical reactors, any design error can cause serious accidents and huge economic losses. Thus knowing the behavior of a system before building it becomes essential. Simulating a chemical reactor involves extensive and complex calculations which most times involves systems equations without analytical solution. In addition most chemical reactor simulation software are commercial and non intuitive, requiring the purchase of very expensive licenses. In this context a software that allows the simulation and design of CSTR reactors in transient state was implemented computationally, so that the user can make an analysis of the influence of the process parameters on results obtained. The software was implemented in Python language, integrating the calculation part with a graphical interface that allows a pleasant and intuitive use. For the development of the program, the odeint function was used, which is part of the scipy package and uses LSODA, developed in FORTRAN. This method was mainly responsible for the program's calculations, while the graphical interface was developed with the PySimpleGUI library. The way to use the software was demonstrated by obtaining the solution of three examples, which show that it was possible to obtain software capable of solving problems for CSTR and Batch reactors. This was done in a dynamic and practical way, making it possible to stratify the data in electronic spreadsheets or graphical analysis.